A termodinâmica que emerge da sala de aula - Oliveira, Thais Rodrigues de (2023)
This work aims to apply the concepts of probability to establish the principles of thermodynamic behavior in macroscopic systems, with the objective of developing an educational product capable of filling a formative gap in high school education. This gap is of significant consequence in higher education courses and in the ability to interpret phenomena or problems involving statistical concepts. We will utilize the classroom as a stage to simulate a macroscopic system of many bodies. Each student will be responsible for conducting random experiments (such as dice rolls, for example), and the individual results will be used to compose the overall class average in various scenarios. With this framework, we demonstrate how individual outcomes play a pivotal role in constructing the global average outcome. This approach serves to introduce the concepts of microstates and macrostates of statistical systems in a playful and constructive manner. The Educational Product was implemented at Leônidas Antero de Matos State School in Cuiabá, MT, with a 2nd-year class of the Regular High School program. The class, consisting of 20 students aged between 16 and 17, participated in the morning sessions. Gamification strategies, employing dice games and card decks, facilitated the incorporation of everyday experiences (games familiar to students) to teach elements of combinatorial analysis, probability, and thermodynamics. We acknowledge that this is indeed a challenging subject; however, preliminary results suggest that the strategies conceived for this project hold promise. Although the obtained results currently lack statistical certainty, based on the application experience, we believe the product has the potential to make a meaningful contribution to the transmission of knowledge regarding probabilistic phenomena and the origins of thermodynamic properties.